Teaching Arabic for Children: A Case Study at Islamic Integrated Elementary School - Yoke Suryadarma; Muhammad Zaki; Fitri Setyo Rini; Siti Nikmatul Rochma (UIN Syekh Wasil Kediri, Indonesia, 2025)
This study aims to examine the implementation of Arabic language teaching at SDIT Qurrota A’yun Ponorogo, with particular attention to instructional methods and challenges encountered in the learning process. Employing a qualitative descriptive approach, the study involved four informants consisting of one school principal and three Arabic language classroom teachers. Classroom observations were conducted in Grades 4, 5, and 6 to capture authentic instructional practices. Data sources comprised primary data obtained from in-depth interviews and direct classroom observations, and secondary data derived from relevant educational documents. Data were analyzed descriptively by Miles and Huberman’s Method to provide a comprehensive portrayal of the instructional context. The findings indicate that Arabic language instruction at SDIT Qurrota A’yun Ponorogo is implemented through an interactive and supportive learning environment that accommodates students’ psychological and cognitive development. Instruction emphasizes the acquisition of basic Arabic language skills using student-centered strategies, including educational games, group activities, and the use of instructional media to enhance comprehension and retention. Nevertheless, variations in students’ learning abilities emerge as a major challenge, particularly in reading and writing skills, necessitating differentiated instructional support. This study contributes new empirical insights into Arabic language instruction at the Islamic primary school level by demonstrating how the integration of Qur’anic reading reinforcement, interactive pedagogy, and adaptive classroom strategies can effectively support early Arabic language acquisition. Penelitian ini bertujuan untuk mengkaji implementasi pengajaran bahasa Arab di SDIT Qurrota A’yun Ponorogo, dengan fokus khusus pada metode pengajaran dan tantangan yang dihadapi dalam proses pembelajaran. Menggunakan pendekatan deskriptif kualitatif, penelitian ini melibatkan empat informan, yaitu satu kepala sekolah dan tiga guru bahasa Arab di kelas. Observasi kelas dilakukan di kelas 4, 5, dan 6 untuk menangkap praktik pengajaran yang autentik. Sumber data meliputi data primer yang diperoleh dari wawancara mendalam dan pengamatan langsung di kelas, serta data sekunder yang diambil dari dokumen pendidikan yang relevan. Data dianalisis secara deskriptif menggunakan Metode Miles dan Huberman untuk memberikan gambaran komprehensif tentang konteks pengajaran. Temuan menunjukkan bahwa pengajaran bahasa Arab di SDIT Qurrota A’yun Ponorogo dilaksanakan melalui lingkungan belajar interaktif dan mendukung yang mengakomodasi perkembangan psikologis dan kognitif siswa. Pengajaran menekankan penguasaan keterampilan dasar bahasa Arab menggunakan strategi berpusat pada siswa, termasuk permainan edukatif, aktivitas kelompok, dan penggunaan media pembelajaran untuk meningkatkan pemahaman dan retensi. Namun, perbedaan kemampuan belajar siswa muncul sebagai tantangan utama, terutama dalam keterampilan membaca dan menulis, yang memerlukan dukungan pengajaran yang dibedakan. Studi ini memberikan wawasan empiris baru tentang pengajaran bahasa Arab di tingkat sekolah dasar Islam dengan menunjukkan bagaimana integrasi penguatan membaca Al-Qur’an, pedagogi interaktif, dan strategi kelas adaptif dapat secara efektif mendukung penguasaan bahasa Arab pada tahap awal.